2015
DOI: 10.1021/np5007907
|View full text |Cite
|
Sign up to set email alerts
|

Depsipeptide Companeramides from a Panamanian Marine Cyanobacterium Associated with the Coibamide Producer

Abstract: Two new cyclic depsipeptides, companeramides A (1) and B (2), have been isolated from the phylogenetically characterized cyanobacterial collection that yielded the previously reported cancer cell toxin coibamide A (collected from Coiba Island, Panama). The planar structures of the companeramides, which contain 3-amino-2-methyl-7-octynoic acid (Amoya), hydroxy isovaleric acid (Hiva), and eight α-amino acid units, were established by NMR spectroscopy and mass spectrometry. The absolute configuration of each comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…Comparison with the derivatized hydrogenated hydrolysate of ulongapeptin established the absolute configuration of the Amoya as 2 S , 3 S [34]. Surprisingly, the absolute configuration of the Amoya unit in companeramides A ( 22 ) and B ( 23 ) was determined to be 2 S , 3 R using the method of Marfey’s analysis in comparison with synthetically saturated 3-amino-2-methyloctanoic acid C-2 diastereomeric (2 R , 3 R and 2 S , 3 R ) standards [35]. …”
Section: Different Methods To Determine the Absolute Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with the derivatized hydrogenated hydrolysate of ulongapeptin established the absolute configuration of the Amoya as 2 S , 3 S [34]. Surprisingly, the absolute configuration of the Amoya unit in companeramides A ( 22 ) and B ( 23 ) was determined to be 2 S , 3 R using the method of Marfey’s analysis in comparison with synthetically saturated 3-amino-2-methyloctanoic acid C-2 diastereomeric (2 R , 3 R and 2 S , 3 R ) standards [35]. …”
Section: Different Methods To Determine the Absolute Configurationmentioning
confidence: 99%
“…Just recently, two new cyclic depsipeptides, companeramides A ( 22 ) and B ( 23 ) containing Amoya unit, were obtained from a marine cyanobacterial assemblage comprising a small filament Leptolyngbya species, from Coiba Island, Panama. It is interesting to note that companeramides A and B showed high nanomolar in vitro antiplasmodial activity, though not quite cytotoxic to human cancer cell lines [35]. …”
Section: Cyclic Peptides Containing Terminal Alkynementioning
confidence: 99%
“…Some metabolites have been isolated from cyanobacterial assemblage without accurate identification of the producer organisms. For these cases, the authors identified the genera of the two dominant cyanobacteria of the assemblage but could not accurately determine which one of them produces which molecule [27][28][29][30][31][32][33][34][35][36][37][38][39]. Tidgewell et al (2010) [9] also identified the prevalence of the marine cyanobacterial products within Oscillatoriales and Nostocales with 58% and 24% of the isolated molecules, respectively.…”
Section: Taxonomy Of the Producing Strainsmentioning
confidence: 99%
“…While partial hydrolysis Marfey's approaches have been used in the past, these have been relatively insensitive (i.e. operating on a 4-15 mg scale acid hydrolysis) 223,225,227 and often relied on the total synthesis, and chromatographic and/or spectroscopic comparison to multiple putative hydrolysis products. 222 Significantly, none of these "partial hydrolysis"…”
Section: Development Of 2d C 3 Marfey's Methodsmentioning
confidence: 99%
“…222 The regiochemistry of L and D-N-Me-Ala in companeramide B (7.14) was determined by a combination of partial acid hydrolysis, followed by HPLC isolation of a diagnostic tetrapeptide fragment, and an Advanced Marfey's analysis. 223 This regiochemical challenge is also well exemplified by kahalalide F (7.15), first isolated in 1993 as an exceptionally potent cytotoxic cyclic peptide from the sarcoglossan mollusc (Elysia rufescens) and its dietary green alga (Bryopsis sp. Marfey's method capable of determining the regiochemistry analytically.…”
Section: Challenges To Determine Regiochemistrymentioning
confidence: 99%